2010
DOI: 10.4314/njm.v19i4.61970
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid cancers amongst goiter population in a Nigerian tertiary hospital: surgical and radiographic perspective

Abstract: Background: Goiters are commonly benign, but cases of malignancy can develop. Thyroid cancer is known to be commoner in whites than in blacks and in females than in males. Bone metastasis is a common occurrence and may be the initial manifestation in a small subset. We hope to determine the incidence and the cervical radiographic patterns of thyroid cancer amongst goiter population in Nigeria. Method: Surgical, histological and radiographic findings in patients with goiter who had thyroidectomy in our hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
2
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
1
2
1
Order By: Relevance
“…It is difficult to attribute the predominant of PTC in this study to any known cause, but the fact that this study was conducted in the southern part of the country located along the coast where there is high intake of iodine rich sea foods may be suggestive. However, the current finding supports previous histological and clinical studies in Ghana [25,26] Nigeria [27] and other parts of Africa [28] that found PTC to be the predominant type of TM, but differs from some studies in other parts of West Africa [29][30][31][32] South Africa [33,34] and North Africa [35] that reported the commonest TM as FTC in iodine deficient regions of the world.…”
Section: Discussionsupporting
confidence: 84%
“…It is difficult to attribute the predominant of PTC in this study to any known cause, but the fact that this study was conducted in the southern part of the country located along the coast where there is high intake of iodine rich sea foods may be suggestive. However, the current finding supports previous histological and clinical studies in Ghana [25,26] Nigeria [27] and other parts of Africa [28] that found PTC to be the predominant type of TM, but differs from some studies in other parts of West Africa [29][30][31][32] South Africa [33,34] and North Africa [35] that reported the commonest TM as FTC in iodine deficient regions of the world.…”
Section: Discussionsupporting
confidence: 84%
“…The high success rate of surgery may be explained by a number of factors, including years of accumulated experience handling thyroid masses. Sex distribution of goiters and the female to male ratio of 12.5: 1 recorded in our study was higher than 4.7: 1 reported from Ethiopia [11],7.3: 1 from a center in India [2],4.4:1 in Nigeria [12], 6:1 reported from South Africa [13] and 7.2:1 seen in Ghana [9]. A higher prevalence of thyroid disorders in females may be attributable to a number of causes, including biological factors and health-seeking behavior among patients.…”
Section: Discussioncontrasting
confidence: 82%
“…In this review malignancy was encountered in 24%, comparable to Hussain's study, reporting 18.3% malignancy 18 . While in contrast Godara observed 8% malignancy and Rahman (Nigeria) 9.3% 22 . In our study papillary carcinoma was diagnosed in 66.67%, follicular carcinoma in 33.33% while Godara 19 encountered papillary carcinoma in 75% and follicular carcinoma in 25%.…”
Section: Discussionmentioning
confidence: 85%